Multivariable interaction analysis for enhanced baby potato (Solanum tuberosum) production in India - SHANKAR, RAJA; MISHRA, ASHOK; NANDEKAR, D N; VERMA, DHARMINDER; GOVINDAKRISHNAN, P M (The Indian Journal of Agricultural Sciences, 2023)
Worldwide, potato is consumed in different forms from cooked to fry, and accordingly the standard cultivars and its production are met. In recent times, the demand for smaller or baby potatoes (Solanum tuberosum L.) with a target size of 20-40 mm in diameter is increasing to meet the culinary market. The production method of baby potato is markedly different from ware potatoes, as are harvested prematurely that led to greater yield reduction per unit area. Hence, a holistic approach is imperative to minimise the yield loss as no single dependent factor operates independently. Therefore, the commercially leading potato cultivars (K. Khyati, K. Himsona, K. Pukhraj and K. Pushkar) were evaluated in AICRP (Potato) under contrasting growing environments for two years to understand the interaction effect of location, cultivars and harvesting time together on yield components. The results revealed a highly significant difference for all three main effects for the entire tuber size production indicated an existence of heterogenity among growing environments and cultivars. The interaction effects location*cultivar and cultivar *harvesting time exhibited a highly significant difference for small (<20 mm), medium (20-40 mm) and large size tuber yield (>40 mm), total yield and tuber dry matter content indicated their strong influence on these traits. The growing location Chinndwara registered substantially greater efficiency by accounting 145, 115, 61 and 97% for small, medium, large size tubers and total tuber yield, respectively. The delay in harvesting time (>75DAP) reduced the per cent of small and medium size tubers and their yield. Although, cv. K. Himsona had the greatest per cent of small and medium size tubers suitable for baby potatoes, the yield of this group was found greatest in cv. K. Khyati and at par with K. Pukhraj across locations, hence can be recommended for baby potato production under tropical conditions.